Hubungan Komunikasi Terapeutik Perawat dengan Kepuasan Pasien di Rawat Inap Rumah Sakit Umum Daerah Pasar Rebo - Siti Safira Annisah; Dwi Rochyani; Dayan Hisni (Malahayati Nursing Journal, 2023)
ABSTRACT Therapeutic communication is a must-have skill for nurses in providing nursing care. If the quality of health services provided by nurses to patients is in accordance with their expectations, there is a feeling of pleasure for the services that have been provided, especially in therapeutic communication because they can establish a trusting relationship between nurses and patients, provide professional satisfaction, and improve the good impression of the nursing profession and hospitals. This study aims to determine the relationship between nurse therapeutic communication and patient satisfaction in inpatient General Hospital Pasar Rebo Area. The design of this study uses a correlation analytical design with a cross-sectional approach. The population in this study was inpatients at Pasar Rebo Hospital. Data collection technique with purposive sampling with a total sample of 80 people. The research instruments used were the nurse's therapeutic communication questionnaire and the patient satisfaction questionnaire. The data analysis used is the Chi-square test. The results showed that therapeutic communication and respondents who expressed satisfaction were 69 people (86,3%). Analysis of Chi-square test data obtained a p-value of 0,000 0,05 which showed that there was a relationship between nurse therapeutic communication and patient satisfaction and OR (Odds Ratio) = 28.438, meaning that respondents perceived therapeutic category nurse therapeutic communication was 28.438 times more likely to get patient satisfaction in the satisfied category compared to therapeutic communication in the non-therapeutic category. There is a relationship between nurse therapeutic communication and patient satisfaction at Pasar Rebo Regional General Hospital. It is hoped that nurses will maintain therapeutic communication so that a trusting relationship between nurses and patients is fostered and provides satisfaction in nursing services. Keywords : Therapeutic Communication, Nurses, Patient Satisfaction  ABSTRAK Komunikasi terapeutik merupakan keterampilan yang harus dimiliki oleh perawat dalam memberikan asuhan keperawatan. Jika kualitas pelayanan kesehatan yang diberikan oleh perawat kepada pasien sesuai dengan harapannya maka muncul perasaan senang atas pelayanan yang telah diberikan terutama dalam komunikasi terapeutik karena dapat terjalin hubungan saling percaya antara perawat dengan pasien, memberikan kepuasan profesional, dan meningkatkan kesan baik profesi keperawatan serta rumah sakit. Penelitian ini bertujuan untuk mengetahui hubungan komunikasi terapeutik perawat dengan kepuasan pasien di rawat inap Rumah Sakit Umum Daerah Pasar Rebo. Desain penelitian ini menggunakan desain analitik korelasi dengan pendekatan cross-sectional. Populasi dalam penelitian ini adalah pasien rawat inap RSUD Pasar Rebo. Teknik pengumpulan data dengan purposive sampling dengan jumlah sampel 80 orang. Instrumen penelitian yang digunakan adalah kuesioner komunikasi terapeutik perawat dan kuesioner kepuasan pasien. Analisa yang digunakan yaitu uji Chi-square.: Hasil penelitian menunjukkan bahwa komunikasi yang terapeutik dan responden yang menyatakan puas sebanyak 69 orang (86,3%). Analisa uji Chi-square diperoleh nilai p-value 0,000 0,05 yang menunjukkan terdapat hubungan komunikasi terapeutik perawat dengan kepuasan pasien dan OR (Odds Ratio) = 28.438, artinya responden yang mempersepsikan komunikasi terapeutik perawat kategori terapeutik ber sebesar 28.438 kali untuk mendapatkan kepuasan pasien kategori puas dibandingkan dengan komunikasi terapeutik kategori tidak terapeutik. Terdapat hubungan antara komunikasi terapeutik perawat dengan kepuasan pasien di Rumah Sakit Umum Daerah Pasar Rebo. Diharapkan untuk perawat agar mempertahankan komunikasi terapeutik sehingga terbina hubungan saling percaya antara perawat dengan pasien serta memberi kepuasan dalam pelayanan keperawatan. Kata Kunci: Komunikasi Terapeutik, Perawat, Kepuasan Pasien